Possible effects of hyperparathyroidism in the loss of osseointegration of dental implants: A case report - Petroni Giulia; Brodocz Lukas Jonathan; Passarett Alfredo; Zanza Alessio; Testarelli Luca; Cicconetti Andrea (Medicinski fakultet i Klinika za stomatologiju, Niš, 2022)
Background: Hyperparathyroidism (HPT) is a common endocrine disorder with potential complications on the skeletal, renal, neurocognitive and cardiovascular systems. Its association with the lack of osseointegration of dental implants has not been described in the medical literature. Case presentation: This case report aims to discuss two cases of dental implant loss in which a high level of parathormone (PTH) was found in the absence of any other systemic or local comorbidity, suggesting the possible correlation between HPT and implant. Both patients were referred to the clinic complaining about prosthetic complications, gingival inflammation and mobility of the dental prosthesis. After a Cone-Beam computed Tomography evaluation, all implants of both patients were removed for rejection arising from periimplantitis and then four implants were inserted in the patient 1 and five implants in the patient 2. For both patients short implants (Bicon LLC, Boston, Massachusetts, USA), featured by 4 mm in diameter and 5 mm in height, were used and the prosthesis substructure was made of Trinia® (Bicon LLC, Boston, Massachusetts, USA). During the fifth year, the patients reported complications and the implant treatment failure. In order to establish the causes of failure, a thorough investigation was performed. Since no causes were detected, the patients were required to perform a blood test to evaluate bone metabolism and specifically to assess parathyroid-hormone levels (PTH), calcium levels and vitamin D. Results: The results of the blood tests showed normal calcemia, vitamin D deficiency and elevated PTH levels in both patients. After an endocrinologist's consultation, secondary hyperparathyroidism was diagnosed. Conclusion: It is reasonable to assume that the loss of osseointegration of dental implants can be correlated with the effects of HPT.